Obstacles in implementing Iraqi environmental laws and policies for air pollution: the case study of Baghdad - Abulkadhim, Asmaa (2016)
Iraq, like many other developing states, has been facing environmental problems including air pollution.To cope with these problems, the Government of Iraq has passed some important environmental laws and policies such as the Ministry of Environment Act 2008, the Protect and Improve Environment Act 2009, Air Protection Order 2012.Iraq has also become party to international environmental treaties.Unfortunately these laws and policies have not been properly enforced due to some problems such as non-implementation, non-coordination, lack of environmental expertise, and weak execution.This paper discusses the constraints of the environmental laws and policies in Iraq to tackle the problem of air pollution. Primary data were gathered from in-depth interviews with participants relevant to the study including environmental professionals, academics and also selected the residents affected by the air pollution.Some recommendations are offered to address this problem.